1998
DOI: 10.1017/s1357729800033063
|View full text |Cite
|
Sign up to set email alerts
|

Feeding value of pea (Pisum sativum, L.) 2. Nutritional value in the pig

Abstract: Nineteen round white-feed peas (FP) varieties, six coloured-flowered peas (CP) varieties and four wrinkled white-flowered peas (WP) varieties were given to growing pigs in order to measure their feeding value. Mean values of energy apparent digestibility measured at the faecal level of FP, CP and WP were respectively 0·886, 0·812 and 0·823. Mean values for digestible energy were 16·34, 1506 and 15·60 M]l kg dry matter. Mean values of faecal apparent digestibility of protein were 0·840, 0·760 and 0·828. The low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
3
10
0
1
Order By: Relevance
“…PdE was not correlated with predicted ileal digestibility of protein (pdN), nor with tannin or nutrient content in seeds. Grosjean et al (1998a) reported that apparent digestibility of energy in pigs was 89%) for white-and 81%o for coloured-flowered pea. The lower pdE value of the Zuraw cultivar was undoubtedly due to the high tannin content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PdE was not correlated with predicted ileal digestibility of protein (pdN), nor with tannin or nutrient content in seeds. Grosjean et al (1998a) reported that apparent digestibility of energy in pigs was 89%) for white-and 81%o for coloured-flowered pea. The lower pdE value of the Zuraw cultivar was undoubtedly due to the high tannin content.…”
Section: Discussionmentioning
confidence: 99%
“…Pea production increased considerably in Europe and many research programmes were established to study the composition of different types and cultivars of pea and relationships between composition criteria and nutritional value of pea (Bastianelli et al, 1998;Grosjean et al, 1998aGrosjean et al, ,b, 1999. In Poland, among seventeen registered cultivars of pea grown on light soils, twelve (Wiatr, 1999) belongs to a colour-flowered (P. sativum L. ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Pea samples were analysed for TSW according to the standard method (AFNOR V 03-702 1988), for HULL according to the method of Munier-Jolain described by Grosjean et al (1998a) and for TIA according to the American Oil Chemists Society method (1983) with results expressed as UTI mg DM -1 allowing calculation of TIAP expressed as UTI mg CP -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Feed peas are used mainly for pigs and, for example, in France, peas represented 22% of the feedstuffs used by the feed industry for pigs between 1990 and 1997 (Bernicot et al 1998). This type of pea, which comes from white-flowered varieties (Bastianelli et al 1998), is more valuable for pigs than other peas, mainly due to the effects of tannins in round, colouredflowered varieties and the high amylose/amylopectine ratio in wrinkled varieties (Grosjean et al 1998a.). However, feed peas exhibit TIA, which may vary between 2 and 15 UTI mg DM -1 (Grosjean et al1993) depending on variety and, to a lesser extent, environmental growing conditions (Wang et al 1998), although most commercial feed peas have TIA lower than 4 UTI mg DM -1 (Grosjean et al 1993).…”
mentioning
confidence: 99%
“…Hlödversson (1987) determinou valores de energia digestível para o grão de ervilha variando de 3752 a 3920 kcal/kg MS, Fan & Sauer (1994) encontraram valores que variaram entre 3346 e 3442 kcal/kg MS, enquanto Grosjean et al (1998) encontraram valor de 3905 kcal/kg MS. Os resultados revisados apresentaram valores de EM em torno de 5% abaixo da ED, diferença correspondente a perdas urinárias esperadas em dietas produzidas com milho e farelo de soja segundo o NRC (1998). No presente estudo, a menor diferença foi de 6,17% para a EM.…”
Section: Resultsunclassified